Explaining the Rate Spread on Corporate Bonds - Elton, Edwin J.; Gruber, Martin J.; Agrawal, Deepak; Mann, Christopher (Journal of Finance, 2001)
ABSTRACT The purpose of this article is to explain the spread between rates on corporate and government bonds. We show that expected default accounts for a surprisingly small fraction of the premium in corporate rates over treasuries. While state taxes explain a substantial portion of the difference, the remaining portion of the spread is closely related to the factors that we commonly accept as explaining risk premiums for common stocks. Both our time series and cross‐sectional tests support the existence of a risk premium on corporate bonds.